PENGUATAN HUMANISASI DALAM PRAKTIK PENDIDIKAN DI SMK SWASTA DI JAKARTA MELALUI PERSPEKTIF PAULO FREIRE - Gopito, Florensia Eka; Siti, Kristina; Freitas, Celia Maria Antonia Da Costa (Jurnal Manajemen Pendidikan, 2025)
Vocational High Schools (SMK) have a strategic role in producing human resources who are ready to enter the world of work. However, vocational schools are also required to form students as fully critical, reflective, and socially caring human beings. This article analyzes educational practices in private vocational schools in Jakarta using the framework of Paulo Freire's humanization and dehumanization theory. This research was conducted with a descriptive qualitative approach through the literature study method, which examines internal school documents, national literature on literacy, and critical pedagogical theory works. The results of the study show that there is an imbalance between the vision of humanist education and daily practices that tend to be dehumanistic. The dominance of lectures, hierarchical relationships between teachers and students, a technically-oriented curriculum, and a weak critical literacy culture are the main challenges. This article offers strategies to strengthen humanization, including the integration of critical-humanistic curriculum, project-based learning, strengthening critical literacy, dialogical classrooms, and teacher capacity building through critical pedagogy. The implications of this study confirm that vocational education should not only focus on the needs of the labor market, but should also function as a vehicle for student liberation and empowerment.